Are the elderly a threat to educational expenditures? - Maria Alejandra Cattaneo; Stefan C. Wolter (Center for Economic Studies and ifo Institute (CESifo), 2007)
Empirical research has given cause to fear that the demographic ageing in industrialized countries is likely to exert a negative impact on educational spending. These papers have linked the share of the elderly with the per capita or per pupil spending on education at the local, state-wide or national level, trying to control for other exogenous effects. Although this line of research shows in many cases a negative correlation between the shares of elderly people and educational expenditures, a causal link is difficult to prove. This paper uses a unique and representative survey of Swiss voters of all age groups. The analysis shows that elderly people present a clear tendency to be less willing to spend money on education. They would rather prefer to spend public resources on health and social security than on education. Furthermore the paper shows that much of the negative correlation between the shares of elderly and educational spending is the result of the elderly being politically more conservative and in general less inclined to pay for expenditures in the public sector as a whole.
Keywords: H52; H72; I22; J18; 330; Öffentliche Bildungsausgaben; Wahlverhalten; Alte Menschen; Öffentliche Ausgaben; Alternde Bevölkerung; Schweiz